Childhood Neurological Illness in Nepal - Mishra, N; Belbase, M; Shrestha, D; Poudel, R; Mishra, P (Journal of Nepal Health Research Council, 2010)
The commonly encountered neurological disorders in Nepalese children are febrile encephalopathies, neurocysticercosis, and epilepsy,and neonatal encephalopathy,neuro-psychiatric and neuromuscular disease. Also, these childrenin Nepal remain one of the most vulnerable andmarginalized groups in the community. Due to the lack of proper facilities some preventable and treatable neurological conditions continue to paralyze thechildren’s physical and mental health. The alarmingly high prevalence of theseneurological illnesses  has high mortality and morbidity in children ultimately adding financial burden to the family, society and the country asa whole. The paucity of data and difficultiesin proper collection of reliable facts further   hampers to understand the actual magnitude of thisproblem.                      Key words: epilepsy,neonatal encephalopathy, neurocysticercosis